The Seasonal Metabolic Activity Cycle of Antarctic Krill (Euphausia superba): Evidence for a Role of Photoperiod in the Regulation of Endogenous Rhythmicity - Piccolin, Fabio; Suberg, Lavinia; King, Robert; Kawaguchi, So; Meyer, Bettina; Teschke, Mathias (Frontiers in Physiology, 2018)
Antarctic krill (Euphausia superba), a key species in the Southern Ocean, reduce their metabolism as an energy saving mechanism to survive during the Antarctic winter. Although the adaptive significance of this seasonal metabolic shift seems obvious, the driving factors are still unclear. In particular, it is debated whether the seasonal metabolic cycle is driven by changes in food availability, or if an endogenous timing system entrained by photoperiod might be involved. In this study, we used different long-term photoperiodic simulations to examine the influence of light regime and endogenous rhythmicity on the regulation of krill seasonal metabolic cycle. Krill showed a seasonal cycle of growth characterized by null-to-negative growth rates during autumn-winter and positive growth rates during spring-summer, which was manifest also in constant darkness, indicating strong endogenous regulation. Similar endogenous cycles were observed for the activity of the key-metabolic enzyme malate dehydrogenase (MDH) and for the expression levels of a selection of metabolic-related genes, with higher values in spring-summer and lower values in autumn-winter. On the other side, a seasonal cycle of oxygen consumption was observed only when krill were exposed to simulated seasonal changes in photoperiod, indicating that light-related cues might play a major role in the regulation of krill oxygen consumption. The influence of light-regime on oxygen consumption was minimal during winter when light-phase duration was below 8 h, while it was maximal during summer when light-phase duration was above 16 h. Significant upregulation of the krill clock genes clk, cry2 and tim1, as well as of the circadian-related opsins rh1a and rrh, was observed after light-phase duration had started to decrease in early autumn, suggesting the presence of a signaling cascade linking specific seasonal changes in the Antarctic light regime with clock gene activity and the regulation of krill metabolic dormancy over the winter.